2012
DOI: 10.18388/abp.2012_2179
|View full text |Cite
|
Sign up to set email alerts
|

Light distributions on the retina: relevance to macular pigment photoprotection.

Abstract: Light exposure has been implicated in age-related macular degeneration (AMD). This study was designed to measure cumulative light distribution on the retina to determine whether it peaked in the macula. An eye-tracker recorded the subject's field of view and pupil size, and superimposed the gaze position. Fifteen naïve subjects formed a test group; 5 formed a control group. In phase 1, all subjects viewed a sequence of photographic images. In phase 2, the naïve subjects observed a video; in phase 3, they perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The distribution of incident light, often invoked as a mechanism behind topographic differences in the retina, is fairly even across the fundus out to 50 deg of eccentricity and thus does not explain variation within the 6 mm diameter macula (21 deg of vision) (Kooijman, 1983; Pflibsen et al . , 1988; Bone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of incident light, often invoked as a mechanism behind topographic differences in the retina, is fairly even across the fundus out to 50 deg of eccentricity and thus does not explain variation within the 6 mm diameter macula (21 deg of vision) (Kooijman, 1983; Pflibsen et al . , 1988; Bone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Such data would provide valuable information on whether such activities can put the retina at risk of light-induced injury. The feasibility of such measurements with an eye-tracker and a camera capturing the images in the visual field was shown already in 2012 by Bone et al but also revealed the challenges of quantitative measurements of the absolute illuminance values using a scene camera with a small dynamic range [525,526]. Overcoming these challenges and adding spectroradiometric measurements and the measurements of the transmission of the lens, would enable the calculation of the spatial distribution of the retinal spectral irradiance in the absolute values.…”
Section: Determination Of Topography Of Retinal Irradiance Under Vari...mentioning
confidence: 99%